PANDANGAN GENERASI Z MENGENAI PERSONAL BRANDING ONLINE FRESH GRADUATES DALAM MENCARI PEKERJAAN - Dewi Rachmawati (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Intense competition between workers to reach a position requires fresh graduates including Generation Z to display their achievements and something unique. Personal branding is something that recruiters consider to recruit. Currently, personal branding is not only seen by recruiters from the Curriculum Vitae (CV) and cover letters sent by applicants, or through interviews, but has also begun to penetrate into tracking applicants' social media. This study aims to find out how Generation Z views online personal branding for themselves and their generation and to find out Generation Z's views on the benefits of online personal branding for themselves for their careers. Researchers used descriptive qualitative methods to obtain comprehensive data. A total of 11 sources of fresh graduates of Generation Z, representing several regions in Indonesia, participated in the Focus Group Discussion (FGD). The personal branding criteria applied in this research are 11 criteria by Hubert K. Rampersard. The results showed that all respondents agreed that online personal branding was very important both for their own needs and in terms of looking for work. In addition, what is displayed on social media should be authentic, describe specialization or uniqueness and advantages and of course what is displayed is useful.